TiO(OH)2 – highly effective catalysts for optimizing CO2 desorption kinetics reducing CO2 capture cost: A new pathway - Hongbao Yao (Nature Portfolio, 2017)
Abstract The objective is to find a new pathway for significant reduction in CO2 capture energy consumption. Specifically, nanoporous TiO(OH)2 was used to realize the objective, which was desired as a catalyst to significantly accelerate the decomposition of aqueous NaHCO3, essentially CO2 desorption – the key step of Na2CO3/NaHCO3 based CO2 capture technologies from overall CO2 energy consumption perspective. Effects of several important factors on TiO(OH)2-catalyzed NaHCO3 decomposition were investigated. The quantity of CO2 generated from 0.238 mol/L NaHCO3 at 65 °C with catalyst is ~800% of that generated without the presence of catalyst. When a 12 W vacuum pump was used for carrying the generated CO2 out of reactor, the total amount of CO2 released was improved by ~2,500% under the given experimental conditions. No significant decrease in the catalytic effect of TiO(OH)2 was observed after five cyclic CO2 activated tests. In addition, characterizations with in-situ Fourier transform infrared spectroscopy, thermal gravity analysis and Brunauer-Emmett-Teller of TiO(OH)2 indicate that TiO(OH)2 is quite stable. The discovery in this research could inspire scientists’ interests in starting to focus on a new pathway instead of making huge effort or investment in designing high-capacity but expensive CO2 sorbent for developing practical or cost-effective CO2 technologies.